Iot health monitoring system for self quarantined covid-19 patients - Vikneswaran, Balakrishnan (2022)
This study focuses fully on the development of a system of monitoring the health data of Covid-19 patients who undergoing self-quarantine by means of data classification. In this Covid-19, we often hear and see on various media platforms as well as social media about many people who suffer from critical dying due to not being able to tell their recent health status. To overcome this problem in society, the creation of prototypes that are able to track the health data of vital signs for Covid-19 self-quarantined patients is very important. How to use this new prototype is like a regular watch that is worn on the wrist. In this invention, if a person falls, the action can be detected because there are several sensors to detect movement. With the invention of this prototype, the symptoms of severe Covid-19 can be detected and make it easier for the patient to receive proper treatment. The main purpose on building this prototype is build a health monitoring system to read the data from vital signs such as heart beat rate, oxygen saturation in blood(SPO2), temperature, GPS location and falling detection. After that vital signs and falling information classified to show caution circumstances. Then develop an IoT system to notify guardian or doctor on emergency situation. The flow of this project will be initializing the system at the first place. Next, the sensors receive the signals and the signals the classified according to the vital signs for Covid-19 patients. After that, the data are saved on the cloud with the help of IoT. On the other hand, if the data classified meets the emergency situation an alert will be notified to doctor or guardian and the process end. There are some main components that have to be used in order to get the accurate vital sign read. At first place Arduino Uno is used as the developer board. Some sensors are also used to complete this prototype such as LM35 temperature sensor which has a more accurate reading than thermistor, ESP8266 Wi-Fi module to transfer data to cloud and save it on cloud, ADXL345 accelerometer, MAX30102 pulse oximeter to count the heart beat rate and oxygen saturation in blood and U-Blox Neo-6m for location tracking. The software used to do coding is Arduino IDE which is suitable for all Arduino boards. Then to get the temperature reading we use some algorithm to calculate the temperature reading from sensor. In Arduino IDE software we can monitor two types of result one is serial monitor and another one is serial plotter. Apart from that to see the output value of heart beat rate, one special algorithm is need to calculate the pulse. The output reading will have BPM value and average value.Next to see the output value of oxygen saturation in blood, one special algorithm is need to calculate SPO2. The output reading will have percentage value and average value.